Second Stage Intervention (Vacuum Versus Forceps) and Maternal Outcome - Syeda Hira Ali Shah, Farha Naz Chohan, Aliya Shamim, Mehwish Zia, Erum Bano, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of the second stage intervention and maternal outcome among those undergoing 2nd stage intervention (forceps versus vacuum) at Liaqat University hospital Hyderabad. Material and methods: This cross-sectional comparative study was conducted at the gynecology and obstetrics department of Liaquat University Hospital Hyderabad during one year from October 2014 to September 2015. Cases having a singleton pregnancy with cephalic presentation as per fresh fetal well-being ultrasound, gestational age 36 weeks or more, undergoing instrumental vaginal deliveries (vacuum or forceps) of either age or parity were included. The position of the head and pelvis and the status of the cervical dilatation were assessed. In the Labor Room, all instrumental forceps and vacuum-assisted deliveries were performed. The time of instrument application, the time of delivery, the type of instrument used, the number of pulls, the number of detachments in the case of ventouse, and the analgesia/anaesthetic provided were all recorded. The consultants who delivered the patient assessed the level of maternal trauma right away. Perineal tears, extension of episiotomy, ulceration of the vagina, cervical tears, and other maternal outcomes were measured. The data were entered and analyzed in the statistical program SPSS version 26.0. Results: During the study period, 2135 pregnant women were identified, with 265 receiving second-stage intervention (14.70%). These women were 27.84+5.13 years old on average. 52.83% women received ventouse/vacuum extraction and 47.16% received forceps assistance. The majority of females 73.58% were un booked. The interval decision-to-delivery was substantially shorter in patients of the forceps group than in the vacuum patient’s group (p-0.0001). Maternal trauma of soft tissues was the most common complication among 58 cases and out of them vaginal tears were significantly higher 18.4% in the Forcep group compared to vacuum group 7.14%, while cervical tear 4% in the Forcep group and 3.57% in the vacuum group and 3rd degree perineal in 8% of the Forcep group and 3.57% in the vacuum group. Findings regarding cervical tear, 3rd degree perineal, PPH, LSCS and other maternal complications were statistically insignificant according to both procedures (p->0.05). Conclusion: It was concluded from this study that maternal outcomes in assisted vaginal deliveries suggested that ventouse application is associated with less maternal complications than with forceps. The frequency of the second stage interventions was observed to be 14.70% and no adverse maternal outcomes were observed.